PEMANFAATAN DAUN AKASIA (Acacia mangium) SEBAGAI SUMBER ENERGI ALTERNATIF PEMBUATAN BIO-BATERAI (JRFES (Jurnal Riset Fisika Edukasi dan Sains), 2022)
The purpose of this research is to use acacia leaves (Acacia mangium) as an alternative energy source for making bio-battery. Acacia leaves are compound leaves consisting of many leaflets that are located opposite each other. Acacia leaves contain saponins, tannins and phenols. This phenolic compound is an acidic compound that is included in the electrolyte that can generate electricity. Utilization of the content contained in acacia leaves can be a solution to create an alternative energy source that is environmentally friendly, namely bio-battery.  This research method is experimental and quantitative.  Parameters observed in this study are potential difference or voltage, battery current, and battery power. From the results of testing and observation, it is known that acacia leaf extract can be used as an environmentally friendly electrolyte in batteries by producing an average potential difference of 5.54 Volts, and an average current of 0.141 Amperes. This acacia leaf extract bio-battery can power the LED lamp for 216 hours and 25 minutes. With this research it is hoped that it can contribute to the development of environmentally friendly batteries to reduce B3 waste, along with the increasing need for batteries in the era of the industrial revolution 4.0. Keywords:Acacia mangium, bio-battery